Potential new fluoroquinolone treatments for suspected bacterial keratitis. Issue 1 (18th July 2022) - Herbert, Rose; Caddick, Mary; Somerville, Tobi; McLean, Keri; Herwitker, Shakeel; Neal, Timothy; Czanner, Gabriela; Tuft, Stephen; Kaye, Stephen B
Abstract : Topical fluoroquinolones (FQs) are an established treatment for suspected microbial keratitis. An increased FQ resistance in some classes of bacterial pathogens is a concern. Some recently developed FQs have an extended spectrum of activity, making them a suitable alternative for topical ophthalmic use. For example, the new generation FQs, avarofloxacin, delafloxacin, finafloxacin, lascufloxacin, nadifloxacin, levonadifloxacin, nemonoxacin and zabofloxacin have good activity against the common ophthalmic pathogens such as Staphylococcus aureus, Pseudomonas aeruginosa, Streptococcus pneumoniae and several of the Enterobacteriaceae . However, because there are no published ophthalmic break-point concentrations, the susceptibility of an isolated micro-organism to a topical FQ is extrapolated from systemic break-point data and wild type susceptibility. The purpose of this review is to compare the pharmacokinetics and pharmacodynamics of the FQs licensed for topical ophthalmic use with the same parameters for new generation FQs. We performed a literature review of the FQs approved for topical treatment and the new generation FQs licensed to treat systemic infections. We then compared the minimum inhibitory concentrations (MIC) of bacterial isolates and the published concentrations that FQs achieved in the cornea and aqueous. We also considered the potential suitability of new generation FQs for topical use based on their medicinal properties. Notably, we found significant variation in the reported corneal and aqueous FQ concentrations so that reliance on the reported mean concentration may not be appropriate, and the first quartile concentration may be more clinically relevant. The provision of the MIC for the microorganism together with the achieved lower (first) quartile concentration of a FQ in the cornea could inform management decisions such as whether to continue with the prescribed antimicrobial, increase the frequency of application, use a combination of antimicrobials or change treatment.